2014
DOI: 10.1111/maps.12305
|View full text |Cite
|
Sign up to set email alerts
|

53Mn‐53Cr dating of aqueously formed carbonates in the CM2 lithology of the Sutter's Mill carbonaceous chondrite

Abstract: Radiometric dating of secondary minerals can be used to constrain the timing of aqueous alteration on meteoritic parent bodies. Dolomite is a well-documented secondary mineral in CM chondrites, and is thought to have formed by precipitation from an aqueous fluid on the CM parent body within several million years of accretion. The petrographic context of crosscutting dolomite veins indicates that aqueous alteration occurred in situ, rather than in the nebular setting. Here, we present 53 Mn-53 Cr systematics fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
(164 reference statements)
2
22
0
Order By: Relevance
“…Jilly et al. () showed that the 53 Mn‐ 53 Cr isotope systematics are well behaved in carbonate minerals in Sutter's Mill, SM 51, suggesting a uniform, homogeneous 53 Mn/ 55 Mn level at (3.42 ± 0.86) × 10 −6 when these carbonates were formed between 4,563.7 ( +1.1 / −1.5 ) Ma. Given that L1 and L2 steps would leach out carbonate fractions selectively (Table ), the observation of Jilly et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Jilly et al. () showed that the 53 Mn‐ 53 Cr isotope systematics are well behaved in carbonate minerals in Sutter's Mill, SM 51, suggesting a uniform, homogeneous 53 Mn/ 55 Mn level at (3.42 ± 0.86) × 10 −6 when these carbonates were formed between 4,563.7 ( +1.1 / −1.5 ) Ma. Given that L1 and L2 steps would leach out carbonate fractions selectively (Table ), the observation of Jilly et al.…”
Section: Discussionmentioning
confidence: 99%
“…Given that L1 and L2 steps would leach out carbonate fractions selectively (Table ), the observation of Jilly et al. () would argue against scenario (3), i.e., 53 Mn was heterogeneously distributed at the leached mineral scales. Support for scenario (4) comes from the observation that L5 (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has, thus, emerged as an important tool to constrain the relative ages of events within the first 20 Ma of solar system evolution when 53 Mn was still extant. Excess 53 Cr relative to terrestrial values has been detected in different types of primitive material such as Ca-Al-rich inclusions or CAIs Allegre, 1985, 1988;Papanastassiou et al, 2005), chondrules (Nyquist et al, 2001a(Nyquist et al, , 2009Yin et al, 2007), ordinary chondrites (Lugmair and Shukolyukov, 1998;Nyquist et al, 2001bNyquist et al, , 2009), carbonaceous chondrites (Birck et al, 1999;Moynier et al, 2007;Gö pel et al, 2015); CI carbonates (Endress et al, 1996;Hutcheon and Phinney, 1996;Hutcheon et al, 1999;Jilly et al, 2014), enstatite chondrite sulfides (Wadhwa et al, 1997), and various achondrites (Lugmair and Shukolyukov, 1998;Nyquist et al, 2001b). Nyquist et al (2009) provided a compilation of 53 Cr ages, along with the ages determined by short-lived decay systems in igneous differentiated meteorites and chondrules from ordinary chondrites.…”
Section: Introductionmentioning
confidence: 96%